Motivation, Emotion, and Systemic Factors in Second Language Acquisition: A Narrative Review - Putri, Cicilia Deandra Maya; HR, Sumarlin Rengko (Lingua : Journal of Linguistics and Language, 2025)
This narrative review synthesizes empirical and theoretical insights on how emotions—such as enjoyment and anxiety—shape language learning. Literature was collected from Scopus, PubMed, Google Scholar, and ERIC using keywords related to emotions, motivation, and affective dynamics in SLA. Positive emotions were found to enhance motivation, cognitive engagement, and communicative competence, while negative emotions, particularly anxiety, constrained attention and memory. Motivation emerged as a mediator linking emotions to achievement, and teacher–student interactions and peer support were identified as key drivers of emotional well-being. Cross-cultural evidence shows that systemic and cultural contexts significantly shape emotional experiences, while technology and affect-sensitive tools reduce anxiety and increase engagement. Policies that integrate socio-emotional learning, teacher training, and culturally responsive practices are essential. Future research should adopt longitudinal and mixed-method approaches to capture the dynamic interplay of emotions in SLA.